Assessing the Quantity and Quality Controls of the Freshwater Lens on a Semi-Arid Coral-Limestone Island in Sri Lanka - Wu, Chen Lester R.; Stigter, Tibor Y.; Craig, Simon G. (Frontiers in Water, 2022)
Uncertainties in the contamination and salinization mechanisms of the freshwater lens (FWL) in the semi-arid coral-limestone aquifer of Delft Island, Sri Lanka threatens water security on the island. The processes governing the quality and distribution of the FWL were therefore investigated through recharge assessment, hydrochemical analysis and geophysical surveys. Potential groundwater recharge zones based on land classification and geology were first identified. A rootzone water balance model was then built, which revealed the spatiotemporal variability of potential groundwater recharge occurring rapidly during the wet season (October to January) and most abundantly on pasture land underlain by yellow and brown sand. Recharge also varied largely between dry and wet years. Where the water table was shallow, intense rainfall in wet years was seen to result in flooding. Geochemical modelling using PHREEQC combined with diagrams (Gibbs, Piper, Stiff) and scatter plots, including stable water isotopes, revealed the meteoric origin of groundwater with salinization mainly caused by seawater mixing and slight evaporation. Findings also suggest that salinization is driven by the island’s low-lying nature (maximum elevation of 6 m above sea level), the low hydraulic heads (maximum of 3.7 m above sea level), the shallow depth of the marine water, the presence of lagoons in the center which are inferred to be in hydraulic continuity with the ocean, and to some extent by unregulated abstraction of groundwater through shallow hand-dug wells. Infiltration of saline water through the root zone possibly due to storm inundations was revealed by high alkalinity (from 3.5 to 8.3 mmol/L HCO3-) combined with high salinity (from 165.4 to 236.3 mmol/L of Cl-) in groundwater samples. Cation exchange showed indications of salinization of wells mostly in low lying areas (minimum Na/Cl value of 0.66), and freshening in areas near the coast with high potential groundwater recharge (maximum Na/Cl value of 1.04). Elevated nitrate concentrations (maximum of 2.55 mmol/L NO3-) in groundwater samples were observed. This suggests that anthropogenic contamination is further threatening the already scarce resource as well as coastal ecosystems that may be groundwater dependent.